PENGARUH LATIHAN INTERVAL TRAINING TERHADAP PENINGKATAN VO2 MAX PADA PEMAIN SEPAKBOLA U-16 TAMBUSAI - Kholid, Abdul; Sinurat, Ridwan; Putra, Muarif Arhas (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
This study began with observations by researchers in the field who saw the ability of endurance or VO2 Max in the Tambusai U-16 Football Player was still low. Seen when players do training on the field and when participating in soccer tournament events. This study aims to determine the Effect of Interval Training (X) Training on Increasing VO2 Max on Tambusai U-16 Football Players (Y). This research was quasi-experimental methods with One-Group Pretest-Postest Design. The population in this study was the Tambusai U-16 Football Players, amounting to 20 players, while the sampling technique used saturated sampling where all populations were sampled. The study design uses the Pre-Test and Post-Test VO2 Max by using the Multistage Fitness Test (bleep test) instrument. Data analysis and testing of research hypotheses using independent t-test analysis techniques with a significant level Î± = 0.05. The results showed that the Interval Training Exercise affected the Increased VO2 Max, where the average score of 38,2 in the Pre-Test increased by 2,7 or 3% to 40,9 in the Post-Test. With statistical results show that (tcount 11.265> t table 1.729). It can be concluded that the Interval Training Exercise affects the Increased VO2 Max of U-16 Tambusai Football Players.